2021
DOI: 10.1108/sef-09-2020-0393
|View full text |Cite
|
Sign up to set email alerts
|

Do government expenditure reduce income inequality: evidence from developing and developed countries

Abstract: Purpose This paper aims to re-examine the impact of government expenditure on income inequality. Existing studies provide mixed results on whether government expenditure reduces or increases income inequality. In this paper, government expenditure is viewed as a tool for redistribution, hence, its impact on inequality is examined. Design/methodology/approach A sample of 122 countries with 91 and 31 countries categorized as developing and developed countries is used. The dynamic panel threshold regression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…The result indicated that a 1% increase in government consumption can spur income inequality by 0.097%, 0.092%, and 0.090% in the simple Model, interactive Model-I, and interactive Model-II, respectively. [ 43 ] also reported the same impact in his most recent study. The government expenditure will increase income inequality, but later on, it will reduce the disparity.…”
Section: Resultssupporting
confidence: 58%
“…The result indicated that a 1% increase in government consumption can spur income inequality by 0.097%, 0.092%, and 0.090% in the simple Model, interactive Model-I, and interactive Model-II, respectively. [ 43 ] also reported the same impact in his most recent study. The government expenditure will increase income inequality, but later on, it will reduce the disparity.…”
Section: Resultssupporting
confidence: 58%
“…A squared term of government expenditure (𝑀𝑀𝑆𝑆𝐺𝐺 2 ) is included to test the quadratic association between government expenditure and inequality. Numerous papers find the nonlinear association between income inequality and public spending such as Guzi and Kahanec (2018) and Sidek (2021). For a robustness check, total government expenditure is disaggregated into education (𝑆𝑆𝐺𝐺𝐸𝐸) and health care (𝐻𝐻𝑆𝑆𝐴𝐴𝐿𝐿𝐻𝐻𝐻𝐻).…”
Section: Methodology the Modelmentioning
confidence: 99%
“…Inflation may reduce the purchasing power of the consumers and therefore affect income distribution (Zheng et al, 2023). We also introduced government spending (government expenditure % of GDP) in our model-the intuition behind introducing this variable is because government's fiscal activity in the form of investment in education, health, infrastructure, and social programs is capable of reducing income inequality (Sidek, 2021). Financial development was measured using credit to private sectors as a percentage of GDP.…”
Section: Datamentioning
confidence: 99%